PENERAPAN PEMBANGKIT LISTRIK TENAGA SURYA UNTUK PENERANGAN DAN SOUND SYSTEM DI MTS MADINATUL ILMI, KECAMATAN MUARA GEMBONG, KABUPATEN BEKASI - Sirojuddin Sirojuddin; Wardoyo; A. Pratama; A. Dian; T. Darapuspita (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract This community service aims to implement Solar Cells as a power source for the electricity needs of some mosques or school activities when the electricity goes out. Where sunlight is absorbed by the solar panels and then converted into DC electricity as a power source for the needs of some mosques or school activities, especially when the power goes out while reducing the cost of the electricity load. Solar panels with a power of 100 WP Monocrystalline type absorb solar energy and then turn it into DC electricity and store it in a 12 VDC battery with a capacity of 65 AH through a 12/24 V solar charge controller with a current of 10A. Furthermore, the electricity in the battery can be used directly to DC, or if the current is AC, it can be changed through an inverter (DC to AC). The input of electric current and voltage can be seen on the change controller monitor, while daily power consumption can be seen on the daily power record. This Community Service Program was held at MTS Madinatul Ilmi, Setia Mekar Village, Muara Gembong District, Bekasi Regency, West Java, on 23 July 2022. This program is expected to help overcome the situation when the electricity goes out for mosques and school activities. Abstrak Pengabdian kepada masyarakat ini bertujuan untuk menerapkan Solar Cell sebagai sumber daya bagi keperluan sebagian listrik masjid atau kegiatan sekolah pada saat listrik mati. Dimana sinar matahari diserap oleh solar panel kemudian dikonversi menjadi listrik DC sebagai sumber daya bagi keperluan sebagian listrik masjid atau kegiatan sekolah terutama pada saat listrik mati sekaligus mengurangi biaya beban listrik. Panel surya dengan daya 100 WP jenis Monorystalline menyerap energy matahari kemudian berubah menjadi listrik DC dan disimpan ke battery 12 VDC kapasitas 65 AH, melalui solar charge controller 12/24 V arus 10A. Selanjutnya listrik dalam battery dapat digunakan langsung ke DC atau bila arusnya AC dapat diubah melalui inverter (DC ke AC). Pemasukan arus dan tegangan listrik dapat dilihat pada monitor change controller, sedangkan pemakaian daya harian dapat dilihat pada record daya hariannya. Program Pengabdian kepada Masyarakat ini diadakan di MTS Madinatul Ilmi, Desa Setia Mekar Kecamatan Muara Gembong, Kabupaten Bekasi Jawa Barat pada tanggal 23 Juli 2022. Program ini diharapkan dapat membantu mengatasi keadaan saat listrik mati untuk keperluan masjid maupun kegiatan di sekolah.